Dinámicas de participación en los estamentos del gobierno escolar: una mirada a través del accionar políticamente agenciante en el Colegio Técnico San Cristóbal Sur (IED) (2022)
This study focuses its reflections on youth participation within the educational context. In this way, it is mainly on the school government as a mandatory stage that, from the normative, allows the possibility in the school, to generate processes of active citizenship construction in the learning of democracy.